Natural variation in freezing tolerance in Arabidopsis thaliana - Zhen, Ying (Kansas State University, 2009)
Elucidating the molecular basis of adaptive phenotypic variation represents a central aim in evolutionary biology. Using the model plant species Arabidopsis thaliana, I studied the intra-specific variation in freezing tolerance among natural accessions across its native range. Considerable variation in freezing tolerance among 71 selected accessions was observed both with and without a prior cold acclimation treatment, suggesting that both differences in cold-acclimation capacity and in intrinsic physiology contribute to this variation. A highly significant positive relationship was observed between freezing tolerance and latitude of origin of these accessions. This clinal pattern of variation is found to be attributable, at least in part, to relaxed purifying selection on CBF/DREB1 genes in the species’ southern range. These CBF/DREB1 genes encode transcriptional activators that play a critical role in the ability of A. thaliana plants to undergo cold acclimation and thereby achieve maximum freezing tolerance. Relative to accessions from northern regions, accessions of A. thaliana from the southern part of their geographic range exhibit significantly higher levels of nonsynonymous polymorphisms in coding regions of CBF/DREB1 genes. Relaxed selection on the CBF/DREB1s in southern accessions also has resulted in mutations in regulatory regions that lead to abrogated expression. These mutations in coding and regulatory regions compromise the function of CBF/DREB1 transcriptional activators during the cold acclimation process, as determined by reductions in rates of induction and maximum levels of expression in the downstream genes they regulate. These mutations could be selective neutral or beneficial in southern accessions depending on whether there is an allocation cost associated with cold acclimation. The fitness benefit and possible allocation cost of cold acclimation was examined in freezing and freezing-free environments using natural accessions exhibiting contrasting abilities of cold acclimation as well as transgenic CBF gene over-expression or knockdown/knockout lines. The extent to which cold acclimation benefits the plant in presence of freezing temperature is revealed, but a cost of cold acclimation wasn’t detected in the absence of freezing temperature under our experimental design, which suggests that these mutations in CBF genes in southern accessions might be neutral to natural selection.
Keywords: Arabidopsis thaliana; Freezing tolerance; Cold acclimation; Cline; Relaxed selection; CBF/DREB1; Biology, General (0306)